2005
DOI: 10.1158/0008-5472.can-05-0858
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Expression of the CTCF-Paralogous Transcriptional Factor BORIS in Normal Cells Results in Demethylation and Derepression of MAGE-A1 and Reactivation of Other Cancer-Testis Genes

Abstract: Brother of the Regulator of Imprinted Sites (BORIS) is a mammalian CTCF paralog with the same central 11Zn fingers (11ZF) that mediate specific interactions with varying f50-bp target sites. Regulated in vivo occupancy of such sites may yield structurally and functionally distinct CTCF/DNA complexes involved in various aspects of gene regulation, including epigenetic control of gene imprinting and X chromosome inactivation. The latter functions are mediated by meCpGsensitive 11ZF binding. Because CTCF is norma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
248
8
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(275 citation statements)
references
References 52 publications
15
248
8
4
Order By: Relevance
“…In addition, we have demonstrated that BORIS as well as NY-ESO-1 expression can be induced in cultured lung cancer cells (but not normal human bronchial epithelial (NHBE) cells) following exposure to the DNA-demethylating agent 5-aza-2 0 deoxycytidine (DAC), the histone deacetylase (HDAC) inhibitor Depsipeptide FK228 (DP), or sequential DAC/DP. Furthermore, we have shown that a CTCF-to-BORISshift in occupancy of the NY-ESO-1 promoter coincides with de-repression of this CT gene in lung cancer cells (Hong et al, 2005); a similar phenomenon was observed for activation of MAGE-A1 in these cells (Vatolin et al, 2005).…”
Section: Introductionsupporting
confidence: 65%
“…In addition, we have demonstrated that BORIS as well as NY-ESO-1 expression can be induced in cultured lung cancer cells (but not normal human bronchial epithelial (NHBE) cells) following exposure to the DNA-demethylating agent 5-aza-2 0 deoxycytidine (DAC), the histone deacetylase (HDAC) inhibitor Depsipeptide FK228 (DP), or sequential DAC/DP. Furthermore, we have shown that a CTCF-to-BORISshift in occupancy of the NY-ESO-1 promoter coincides with de-repression of this CT gene in lung cancer cells (Hong et al, 2005); a similar phenomenon was observed for activation of MAGE-A1 in these cells (Vatolin et al, 2005).…”
Section: Introductionsupporting
confidence: 65%
“…The appearance of common CTA (including BORIS) during gametogenesis and tumorigenesis prompts the hypothesis that induction of the gametogenetic programme in somatic cells may be associated with tumour development (Old, 2001;Kalejs and Erenpreisa, 2005). As BORIS seems to function as an upstream regulator for several CTA Vatolin et al, 2005), it is tempting to speculate that BORIS could be the 'master switch' in the process of cell reprogramming, which can guide the epigenetic machinery to a set of target genes eventually leading to their activation. It is important to note that BORIS may also act as an activator of genes responsible for proliferation in particular tissues, such as ER and PR genes in mammary glands.…”
Section: Discussionmentioning
confidence: 99%
“…This chromosome region is often amplified in many cancers and is believed to contain a dominant immortalising or transforming gene(s) (Tanner et al, 1994;Cuthill et al, 1999). Recent reports show that BORIS is a downstream regulator of cancer -testis genes: expression of BORIS in normal cells leads to derepression of cancer -testis genes MAGE-A1, NY-ESO-1 and others Vatolin et al, 2005).…”
mentioning
confidence: 99%
“…Bien que l'on ne connaisse pas précisément le rôle de BORIS au cours de la spermatogenèse, il est probable qu'il soit impliqué dans la régulation de l'expression d'autres gènes spécifiquement impliqués dans les voies de signalisation propres à la spermatogenèse, qui normalement sont aussi réprimés dans les cellules somatiques. L'expression illégitime de BORIS a été détectée dans un nombre significatif de cancers [7][8][9][10][11]. De manière intéressante, l'activation de BORIS dans les cellules somatiques induit l'expression d'autres facteurs C/T (pour cancer/testis), plus particulièrement celle des gènes MAGE-A [7] et de CTAG1/NY-ESO1 [12].…”
Section: Le Rôle De Borisunclassified
“…L'expression illégitime de BORIS a été détectée dans un nombre significatif de cancers [7][8][9][10][11]. De manière intéressante, l'activation de BORIS dans les cellules somatiques induit l'expression d'autres facteurs C/T (pour cancer/testis), plus particulièrement celle des gènes MAGE-A [7] et de CTAG1/NY-ESO1 [12]. Dans ce dernier cas, BORIS recrute le facteur de transcription SP1 au promoteur de CTAG1 pour déréprimer sa transcription [13].…”
Section: Le Rôle De Borisunclassified